Effectiveness of the RME (Realistic Mathematical Education) Approach to Learning Achievement in View of Students' Mathematic Reasoning - Ardiniawan, Dimas Yuniar; Subiyantoro, Slamet; Kurniawan, Sandra Bayu (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study is expected to collect objective information and analyze the potential differences in improving mathematical reasoning abilities between students taught using the Realistic Mathematics Education (RME) approach and students who received conventional learning. The research used a quantitative quasi-experimental method conducted at a public elementary school in Pacitan District. The results of this study indicate that the use of the Realistic Mathematics Education (RME) approach significantly improves students' mathematical reasoning abilities. In particular, students with high mathematical reasoning abilities experienced more significant improvements than those with medium and low mathematical reasoning abilities.